Development of Functional Beverages Based on Sorghum (Sorghum bicolor) Sap Through Controlled Fermentation - Sonya Titin M Nge; Apriliana Ballo (Postgraduate, University of Mataram, 2025)
The use of sorghum is currently limited to its basic potential, particularly the sorghum grain, which is used as a food ingredient. Sorghum stalks, which produce sap, are typically used as animal feed because they have no economic value. Sorghum is commonly consumed in the form of porridge, bread, chips, and drinks. However, so far, sorghum stalks have only been used for animal feed. Sorghum sap derived from sorghum stalks can be used to make wine, as its composition is higher than sugarcane sap. Wine is made through a fermentation process with the help of Saccharomyces cerevisiae. This study aims to determine the alcohol and glucose levels, organoleptic properties, and polyphenol levels. This study used a Completely Randomized Design (CRD). In this study, the fixed variables used were the glucose content of raw materials, the type of yeast, and pH, while the variable that changed was the % volume of the starter. The experiment was carried out by preparing sorghum sap, then the sorghum sap was poured into an Erlenmeyer flask with nutrients, and added starter (5%, 6%, 7%, 8%, 9%, 10%), operating 21 days and pH 4.3 then analysis of alcohol content and glucose content. The results showed that at % volume of starter 10% and fermentation time 21 days gave the highest alcohol content of 19.5%, glucose content 5.8 brix and total polyphenols 0.3449 mg/mL.